Social Loafing Behavior in Group Task Completion of University Student - Charin Elechia Riwoe; Mariana Dinah Ch. Lerik; Juliana M. Y. Benu (Universitas Nusa Cendana, 2022)
A student is a person or group of people who are currently studying at a university, of course, students have duties and responsibilities that must be completed. One of them is a group task. Tasks in groups should be able to help the performance of the group, but social loafing is often found when doing group work. This study aims to see the description of social loafing behavior in group task completion among Nusa Cendana University students. This research is descriptive quantitative research. Participants in this study were 379 students aged 18-25 years. The result showed hows the behavior of social loafing in group assignments completion at Nusa Cendana University students is in the medium category. This shows that Undana students experience social loafing when working on group tasks but can still contribute to the group.